(untitled) (Biological Sciences - PJSIR, 2008)
A simple and sensitive method is described for the determination of buspirone hydrochloride in bulk drug and in formulations employing spectrophotometric technique. The method is based on the interaction of buspirone hydrochloride with ammonium molybdate in acidic media and the absorbance is measured at 700 nm. Beer’s Law is obeyed in the range of 5 mg to 350 mg/ml and RSD is 0.96 % for buspirone hydrochloride. Analytical data for the determination of pure compound is presented along with the application of the proposed method for the analysis of pharmaceutical formulation.